(untitled) (Experimental biology, 2015)
Nanomedicine is created by the fusion of nanotechnology and medicine. It is one of the most promising pathways for the development of novel strategies of the therapy of serious and widespread diseases. For the first time we proposed to construct the medicine delivery system from negative charged PI liposomes. The created system we are named them as PI nanocapsules, because they have the size less than 1 mkm. The created PI nanocapsules did not cause undesirable and any adverse reactions of the organism. We developed methods of the effective loading PI nanocapsules by medicines which was protected by patent of Republic of Kazakhstan. Also there was prepared the nano ointments by mix of nanocapsules with lanolin. For therapy of disease the prepared nano ointments were rubbed on the skin on the area of the sick organ. Has been shown high efficiency nano ointment for the therapy of serious diseases such as ischemic heart disease, diabetic foot, glaucoma and arthritis.